Control of Fungal Diseases and Fruit Yield Improvement of Strawberry Using Bacillus velezensis CE 100 - Sarah Hong; Tae Yoon Kim; Sang-Jae Won; Jae-Hyun Moon; Henry B. Ajuna; Kil Yong Kim; Young Sang Ahn (Microorganisms, 2022)
Due to the increasing health and environmental risks associated with the use of fungicides in agriculture, alternatives—such as using plant growth-promoting bacteria (PGPB) to suppress phytopathogens—that simultaneously improve plant yield, are important. This study evaluated the biocontrol efficiency of Bacillus velezensis CE100 against Macrophomina phaseolina and Fusarium oxysporum f. sp. fragariae, the respective causal agents for charcoal rot and fusarium wilt diseases in strawberry, and its potential to enhance strawberry growth and fruit production. B. velezensis CE 100 produced fungal cell wall-degrading enzymes, chitinases, and β-1,3-glucanases; and inhibited the mycelial growth of M. phaseolina and F. oxysporum f. sp. fragariae by 64.7% and 55.2%, respectively. The mycelia of both phytopathogenic fungi showed severe swelling and rupturing of the hyphae compared to the smooth, normal growth in the control group. Moreover, B. velezensis CE100 produced up to 2.8 units/mL of indole-3-acetic acid (IAA) during incubation and enhanced root biomass in strawberries. Consequently, B. velezensis CE 100 not only increased the fruit yield of strawberries by controlling the fungal diseases but also through enhancing plant growth. The findings of this study indicate that B. velezensis CE100 could be a safe, ecofriendly biocontrol alternative to chemical fungicides in strawberry production.